Pilihan Materi Pembelajaran Guru Pjok SMA dalam Memenuhi Tuntutan Kompetensi Dasar Kurikulum 2013 - Diharjo, Muhammad Zaenudin; Wiguno, Lokananta Teguh Hari (Sport Science and Health, 2021)
Abstract: The purpose of this study was to determine the choice of learning materials for PJOK SMA teachers and what are the obstacles that occur in the learning process. This research uses survey research method.. From the results of data analysis, it was found that the choice of learning materials for high school PJOK teachers in Purwosari District and Sukorejo District, Pasuruan Regency, got a grade X percentage of 37.40% which was in the unsuitable category and 45.45% for class XI was included in the inappropriate category. It can be concluded that the choice of learning materials for high school PJOK teachers in meeting the demands of basic competencies in the 2013 curriculum in Purwosari and Sukorejo districts for class X is in the inappropriate category and for class XI is in the less appropriate category. This is influenced by several factors, namely: (1) facilities and infrastructure, (2) school regulations, (3) teacher competence.Â Abstrak: Tujuan penelitian ini adalah untuk mengetahui pilihan materi pembelajaran guru PJOK SMA dan apa saja hambatan yang terjadi dalam proses pembelajaran. Penelitian ini menggunakan metdoe penelitian survei. Dari hasil analisis data, diperoleh hasil bahwa pilihan materi pembelajaran guru PJOK SMA di Kecamatan Purwosari dan Kecamatan Sukorejo Kabupaten PasuruanÂ  mendapat persentase kelas X sebesar 37,40% termasuk kategori tidak sesuai dan untuk kelas XI sebesar 45,45% termasuk dalam kategori kurang sesuai. Dapat diambil kesimpulan bahwa pilihan materi pembelajaran guru PJOK SMA dalam memenuhi tuntutan kompetensi dasar dalam kurikulum 2013 di Kecamatan Purwosari dan Kecamatan Sukorejo untuk kelas X termasuk dalam kategori tidak sesuai dan untuk kelas XI termasuk dalam kategori kurang sesuai. Hal tersebut dipengaruhi beberapa faktor yaitu: (1) sarana dan prasarana, (2) peraturan sekolah, (3) kompetensi guru.